(untitled) (Prithvi Journal of Research and Innovation, 2025)
This study explores the professional identities of part-time teachers working within Tribhuvan University, focusing on their personal narratives and lived experiences. I use the narrative inquiry method for data collection. I conducted in-depth interviews with the three part-time teachers under the Faculty of Education at Prithvi Narayan Campus, Tribhuvan University, Pokhara. In addition to the narrative interview, I have also used the narrative memos based on the field notes and informal conversations as supplementary sources of information. A reflexive thematic analysis is used to analyze the data. This study concludes that the professional identities of part-time teachers are multifaceted, dynamic, and contextual, particularly within the context of precarious work. The professional identities of university teachers are shaped by the institutional policy of the university and other situations, such as limited job opportunities in the country. The study identifies four major identities of part-time teachers, which include: the resilient identity – shapes through ongoing negotiation demonstrating it as a dynamic and lifelong process between their present struggles and future aspirations; the marginal identity – that marginalize them relies on the tension between teachers’ personal values and institutional structures; the adaptive identity – shapes through the negotiation as their survival strategy for being university teachers between their future aspirations, and institutional policies that teachers use; and the fragmented identity – disjunctions between their aspirations for professional upliftment in university teaching and the reality of an unstable work environment created by limited recognition, job insecurity, and a lack of stability. These four identities do not follow a linear path; instead, they evolve, shape, and reshape over time and across different places.